2020
DOI: 10.3390/e22010115
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Exergy Evaluation of a Two-Stage Axial Vapour Compressor on the LNG Carrier

Abstract: Data from a two-stage axial vapor cryogenic compressor on the dual-fuel diesel–electric (DFDE) liquefied natural gas (LNG) carrier were measured and analyzed to investigate compressor energy and exergy efficiency in real exploitation conditions. The running parameters of the two-stage compressor were collected while changing the main propeller shafts rpm. As the compressor supply of vaporized gas to the main engines increases, so does the load and rpm in propulsion electric motors, and vice versa. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…is the total energy fl ow of any fl uid stream and is the total exergy fl ow of any fl uid stream. Both of these variables are defi ned according to [54,55]:…”
Section: Overall (General) Equations and Balances / Ukupne (Opće) Jed...mentioning
confidence: 99%
“…is the total energy fl ow of any fl uid stream and is the total exergy fl ow of any fl uid stream. Both of these variables are defi ned according to [54,55]:…”
Section: Overall (General) Equations and Balances / Ukupne (Opće) Jed...mentioning
confidence: 99%
“…Thermodynamic performance is best evaluated using exergy analysis because it provides more insights and is more useful in efficiency-improvement efforts than energy analysis alone [64,65]. For any observed control volume, exergy analysis shows performance in relation to the environment [66,67], while energy analysis did not have any relation with the environment in which control volume operates [68][69][70]. Therefore, in the scientific and professional literature can be found that many researchers selected exergy analysis instead of energy analysis for researching the operation of various control volumes or systems [71][72][73].…”
Section: Exergy Analysis Equationsmentioning
confidence: 99%
“…The specific exergy from Equation (8) at standard ambient state of 0.1 MPa and 25 • C is taken as per the recommendations in [36][37][38]:…”
Section: Thermodynamic Analysismentioning
confidence: 99%